2010
DOI: 10.1007/s10956-010-9254-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Career Choice: Comparison Between Students from Computer and Other Disciplines

Abstract: The number of student enrolments in computer-related courses remains a serious concern worldwide with far reaching consequences. This paper reports on an extensive survey about career choice and associated motivational factors amongst new students, only some of whom intend to major in computer-related courses, at two South African universities. The data were analyzed using some components of Social Cognitive Career Theory, namely external influences, self-efficacy beliefs and outcome expectations. The research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(54 citation statements)
references
References 18 publications
2
51
0
1
Order By: Relevance
“…This particular paper has not explored the issue of career advice although the data set does include information regarding this. We will limit our remarks here to say that computing is a relatively new subject area compared to most other career choices and may be suffering from limited career guidance at school with the result that potential students depending on information from the media and advice from friends and family regarding computing careers while relying on school and university far more for advice on other careers [3]. Our research results calls for an ICT career guidance partnership with high schools and tertiary institutions.…”
Section: Interest and Securitymentioning
confidence: 96%
“…This particular paper has not explored the issue of career advice although the data set does include information regarding this. We will limit our remarks here to say that computing is a relatively new subject area compared to most other career choices and may be suffering from limited career guidance at school with the result that potential students depending on information from the media and advice from friends and family regarding computing careers while relying on school and university far more for advice on other careers [3]. Our research results calls for an ICT career guidance partnership with high schools and tertiary institutions.…”
Section: Interest and Securitymentioning
confidence: 96%
“…In addition, Alexander et al (2011) find that women appear to take the advice of others more (mainly their family) when choosing what to study. This is congruent with the data found by Anguelova (2001), according to which women let themselves be guided more by external factors when choosing a technical career, while men make a choice because of their intrinsic interest in the job.…”
Section: Introductionmentioning
confidence: 92%
“…Therefore, they do not always make the decision with the seriousness of thought required and often fail to avail themselves of the opportunities offered by the education and university system itself such as "Open Day at University", career guidance at school, etc. (Alexander et al, 2011). But everyone is interested in making deci-sions that have positive results, and choosing a career is a matching process, where the person matches his/her personal needs with the field that best fits them (Parsons, 1909;Anguelova, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Only a very small proportion of student candidates regarded the financial aspect as the reason for applying -high salaries in the IT field were mentioned by only 3.3% and bigger scholarships by 0.3% [29]. Other studies, too, have revealed that students enrolled in computer related curricula tend to assign less importance to their future salaries compared with other students [31]. At the same time, some studies have also shown that receiving financial support increases the probability of students finishing their studies [16], [18].…”
Section: B Entering Universitymentioning
confidence: 99%